Model Regulasi Diri dalam Pengembangan Karakter Religius MIN 1 Jombang - Ni'matul Izza; Ahmad Giri Ainuddin Muhammadi (AN NUR: Jurnal Studi Islam, 2021)
Religious character development as a conscious effort designed to assist individuals in developing knowledge, skills, and personality in religious character. There are four values in the implementation that are applied in elementary schools that must be developed, namely, worship obedience, gratitude behaviour, praying before and after carrying out activities, tolerance in worship. Good self-regulation by self-regulating affects the process of a religious character that is carried out in life. This study aims to describe the development of religious character in MIN 1 Jombang and to describe the regulation model of MIN 1 Jombang students in carrying out mandatory worship. The research method used in this research is descriptive qualitative which intends to understand the main phenomena in character development and to describe the regulation model of MIN 1 Jombang students. The findings that can be presented are, the self-regulation model of students at MIN 1 Jombang in maintaining the istikamah to perform worship, namely the external regulation model, which is a model that is influenced by other people to run it, and the existence of this influence which then encourages students to carry out every time and continuously and becomes a habit, the self-regulation model turns into an intrinsically motivated behaviour model in which he feels that worship is a very valuable activity that needs to be done.